Multilevel Intervention Model to Improve Nutrition of Mother and Children in Banyumas Regency - Kusumawati, Erna; Rahardjo, Setiyowati; Sistiarani, Colti (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
The community nutrition improvement with main focus on pregnant women and children up to the age of 2 years old need to be done by a cooperation across sectors. Multilevel promotion is a comprehensive intervention and modify the determinant factors. We used multilevel promotion with MATCH (Multilevel Approach to Community Health) to modify determinant factors in various levels i.e. mother, family, community, and policy that related to nutritional status of children. This research was conducted in Banyumas and Kembaran II Community Health Center working area because the nutritional problems in this area were complex, such as low exclusive breastfeeding coverage, low birth weight, and underweight children problems. This study used a quantitative analytic design with cross sectional approach. The population used for this research were pregnant women, toddler’s mother, and their family. The number of sample in this research was 100 people of each population. The data was analyzed by univariate analysis to determine the intervention model of children nutrition improvement in mother’s level. The effectiveness of intervention model was tested by bivariate analysis using dependent t-test. The result of this research were formulated into nutrition improvement model for mother and children through facility identification, approach, media, and information needed. There was a significant difference in knowledge of mother before and after intervention.